Desarrollo de una herramienta para el diseño de un sistema de remoción de sulfuro de hidrógeno presente en el biogás empleando lana de acero (2020)
The following project is a research about the removal of hydrogen sulfide (H2S) for a partial purification of biogas using steel wool. For this purpose, was obtained biogas with a concentration of 11006.64 ppm y 10492.375 ppm of H2S from two batch biodigesters called in the text as R-B1 and R-N1. For the removal of H2S from the biogas produced, the implementation of a fixed bed adsorption column that has steel wool as an adsorbing substance was recommended due to its ease of access. For this reason, a tool developed in Excel is proposed that allows the design of fixed-bed columns, which have as their only inputs the flow of biogas (Q) and the mass of adsorbent (steel wool), variables that are obtained by apply a methodology that is explained in detail and is based on a two-variable Doehlert matrix design that minimizes the concentration of H2S in the biogas at the outlet of the column. Finally, the tool developed in Excel was presented as a quick alternative for the design of an H2S removal column which implements mathematical models, based on the mass balance and equilibrium relations for the calculation of rupture curves.